Implementing a successful SOA Pilot Program best practices for selecting and deploying SOA projects. - Foody, Dan (SOA webservices journal.)
Day by day, company by company, IT organization by IT organization, today's enterprise is busy architecting for business-solution agility and the alignment of key assets around the emerging service-oriented architecture (SOA) umbrella. The ability to embrace SOA leads to the ability to rapidly capitalize on future IT investments and leverage existing technologies both inside and outside of your organization. Many organizations will struggle as they seek to identify, implement and build on their first SOA forays into the new environment. This is unfortunate, because a number of best practices and lessons learned can be applied from the past and the growing SOA experience from technology providers and practitioners. As organizations work to extend IT capabilities utilizing SOA, many choose to implement a key first step : a pilot program, which enables the greater understanding and methodological deployment of Web services and SOA around a structured initiative.